Which horticultural activities are more effective for children’s recovery from stress and mental fatigue? A quasi-experimental study - Guo, Le; Xu, Wei; Shi, Yuyi; Gao, Shuguang; Xiao, Chengxiang; Zhang, Xiaoxiao; Liu, Xifan; Zhang, Qingyu; Zhang, Yanlong (Frontiers in Psychology, 2024)
Introduction Studies have established the benefits of horticultural therapy and activities for human health and well-being. Nonetheless, limited research has been conducted on the potential restorative advantages and distinctions between different types of horticultural activities in terms of stress reduction. Methods This study employed a quantitative research method to investigate the stress recovery benefits of five horticultural activities (flower arrangement, sowing and transplanting seeds, kokedama crafting, pressed flower card making, and decorative bottle painting with dried flowers) and one reference activity (short composition writing) for children. The experiment was conducted in a children’s activity center’s multi-purpose classroom with 48 elementary students aged 9–12 years. The subjects first took a stress test to induce stress and then engaged in horticultural activities for 20 min. Physiological stress was assessed using electrocardiograms and electroencephalograms as feedback indicators. Psychological and emotional changes were determined using the Positive and Negative Affect Schedule for Children and Self-Assessment Manikin scales. Results The results demonstrated that horticultural activities greatly reduced physiological fatigue, and their recovery benefits were significantly greater than those of the reference activity. The recovery effects from different horticultural activities were similar across physiological indicators, although flower arrangement and sowing and transplanting seeds exhibited relatively robust recovery benefits. The heart rate and α-EEG-based generalized estimating equation revealed that horticultural activities offered significantly better relative recovery at each time phase of operation than the reference activity, with girls showing a 3.68% higher relative recovery value than boys. Flower arrangement and kokedama crafting offered better physiological recovery for students with prior horticultural experience, and these two activities received the highest scores in terms of positive effects and the “pleasure” dimension. Students believed that participating in horticultural activities resulted in a noteworthy increase in personal confidence and a greater sense of achievement. Conclusion The study suggests that horticultural activities that involve real and vibrant plants or natural materials and are more attractive have more stress-relieving benefits. We conclude that horticultural activities are beneficial leisure activities that aid in stress relief for children and that it is important to consider the attributes of activities when developing horticultural programs for elementary students.